Locally, Regionally and Nationally Online: Online News Comments Sections as Public Arenas in Geographically Anchored Media Structures - Kangaspunta, Veera (Javnost-The Public, 2020)
This article examines online news comments sections as both representing an example of and a subject concerning changing media structures, the changing relationship between users and media outlets, the way this relationship is influenced by the (changing) understanding of place and, especially, the way users participate in the new public arenas provided by geographically anchored online media sources. The focus is on Finnish online media in its golden era, the early 2010s. The analysis of user comments left in the comments sections of a small local newspaper, a regional newspaper and a national newspaper suggests that geography matters. Comments sections serve as public arenas for discussions of shared issues, specified through geography, and construct public spheres. Especially in the local context, the meaning of such public arenas should not be underestimated.